Levantamiento geológico estructural del tramo de la vía panamericana, Balsas - Tinajas, cantón Balsas, provincia del Oro, escala 1:10 000 - Cajamarca Jaramillo, Ricardo Fabricio (2022)
This research job "Structural geological survey of the section of the Panamericana highway, Balsas - Tinajas, canton Balsas, El Oro Province, scale 1:10 000", It has a road extension of 9 km, making the study polygon covers an extension of 488 ha. The information survey began in the office with photo-interpretation work, generation of topography of slopes, water network of the study area, these basic inputs give me the opportunity to be able to do the development of the structural geological survey in the field visit. The start-up of this investigation gave the lithology of the area in which I can identified two units, which ones correspond to the Plutón de Marcabelí (TrMb) of a Triassic age, that in the field campaign were determined two types of rocks inside this unit like granodiorite rocks and orthogneiss. These rocks dues to various environmental factors, they show high weathering. The unit El Tigre (PZTt) of an initial Paleozoic age, in which sedimentary rocks predominate in the study area and according to the research of Pilatasig, Gordon, Palacios & Sánchez in the Andean multinational project: geosciences for Andean communities Ecuador-Peru-Canada, said that this type of sedimentary materials found in the unit El Tigre, such as siltstones, shales, greywackes, sandstones, observed throughout the study area, they are assigned an Upper Cretaceous age, the which establishes that it would be probably be related to the erosion of continental blocks corresponding to the rocks of the South American craton. In the structural part of the field, I have found a diversity of structures, given mainly due to the plutonic activity that occurred at the time, it has leaved evidence in the strong dips of the shale, and finding folds in that evidenced a family of orthogonal type diaclases and parallel in the shales and granodiorite. I have observed a dextral type fault, also, three inferred faults and a reverse fault. For the development of the inventory in mass, I began for the photo interpretation, identifying on orthophotos (2010) provided by SigTierras the possible mass movements for later identify and corroborate in the field campaign, detailing their information in the file, made to inventory these events. After that, I made the field campaign by defining a structural geological map of area´s study, which includes a synthesis of the aspects previously observed in the field and analyzed in order to obtain complete information regarding the topography, lithology, structures, geology, of the reality presented the road from Balsas to Tinajas. Finally, on the established basis of the local geological map, I have provided the realization of the inventory map of mass movements, it contemplates the most relevant data of the typological characteristic of how the movement developed and the area of affectation in m2, developed under the Datum WGS 84. Keywords: Lithology, Structural Geology, Mass Movements, Balsas, Roads.